2022
DOI: 10.1111/jonm.13652
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between risk perception of COVID‐19 and job withdrawal among Chinese nurses: The effect of work–family conflict and job autonomy

Abstract: Aim The aim of this study was to examine the mediating role of work–family conflict and the moderating role of job autonomy on the association between risk perception of COVID‐19 and job withdrawal among Chinese nurses during the initial disease outbreak. Background Nurses' job withdrawal can not only reduce the quality and efficiency of care but also give rise to turnover during the COVID‐19 pandemic. Thus, it is essential to clarify how and when the risk perception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
18
1
Order By: Relevance
“…Karakose et al [ 59 ] found that heightened COVID-19 phobia and low life-satisfaction levels predicted high WFC and FWC among Turkish school administrators during the COVID-19 pandemic. Liu et al [ 61 ] showed that risk perception of COVID-19 contributed to nurses’ job withdrawal via WFC during the pandemic. Zou et al [ 57 ] found positive relationships between WFC and depression among Chinese parents.…”
Section: Discussionmentioning
confidence: 99%
“…Karakose et al [ 59 ] found that heightened COVID-19 phobia and low life-satisfaction levels predicted high WFC and FWC among Turkish school administrators during the COVID-19 pandemic. Liu et al [ 61 ] showed that risk perception of COVID-19 contributed to nurses’ job withdrawal via WFC during the pandemic. Zou et al [ 57 ] found positive relationships between WFC and depression among Chinese parents.…”
Section: Discussionmentioning
confidence: 99%
“…Two waves of data are collections of the same type of data on the same sample at different times, with only a single variable changing between collections, which can reduce variance in common methods (Podsakoff et al, 2003). This design method has been applied to nursing management studies (Liu et al, 2022; Sweeney et al, 2022), especially the study on the improvement effect of emerging technology, such as robots (Huang et al, 2022), on nursing management. The first‐wave data were collected from patients' daily nursing records before AI technology was deployed, while the second‐wave data were collected after AI technology was introduced.…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have found that safety performance is heavily influenced by stress-related variables such as work-family conflict and job burnout (for a comprehensive review, please see below for a full review). While these problems were also common during the pandemic [ 7 , 8 , 9 , 10 ], there are relatively few studies on how they were linked with safety performance during the outbreaks of COVID-19. In this study, we focus on several important variables that may have influenced the safety performance of subway workers during the first wave of the COVID-19 pandemic (from February 2020 to July 2020).…”
Section: Introductionmentioning
confidence: 99%